Elaboration of Medicine Meta-Profiles - Youttiroung, Bounchan (Archīum Ateneo, 2019)
The Medicine working group had representatives from various levels of academia, including early career lecturers, professors, and deans of the respective institutions. The representation was also diverse in terms of specialities: clinicians, basic medical scientists, public health specialists and medical educators. This diversity of representation provided a rich source of perspectives in meta-profile development. Through an iterative process which involved group discussion, proposing ways of grouping the generic competencies, and creating various graphic representations and conceptual constructs, the group agreed on six domains under which to classify the 13 generic competencies. These six domains were: 1) ethics & professionalism,2) quality assurance, 3) knowledge & skills, 4) communication, 5) family, community & population care, and 6) patient care. These six domains represented the collective perception about what physicians needed to be taught and learn in order to perform their job effectively. For example, there was consensus that physicians needed to be persons of integrity, duty-bound to conductthemselves with integrity, compassion, and professionalism at all times. They had to have the expertise to minister to their patients and constituencies while cognizant of their own personal limitations. They had to communicate effectively and to maintain the trust of those who sought their care and counsel.